Pyogenic Discitis in Female after Delivery and Pelvic Surgery - Shalal, Maad M; Al-Mukhtar, Sadiq A. (AL-Kindy College Medical Journal, 2007)
Background: Pyogenic discitis most frequently occurs after home delivery, hemorridectomy, and dilatation and curettage. Discitis is generally due to blood borne bacterial invasion of the disc from adjacent end-plate via communicating vessels. Infective discitis remains an uncommon, but potentially serious cause for back pain. Delayed diagnosis can occur and a high index of suspicion may occur. Methods: The study included 30 patients suffering from localized low back pain with limitation of movement. Diagnosis was made by history, physical examination and investigation mainly E.S.R and MRI. Results: 50.3% of patient with discitis had a history of vaginal delivery, 15% had a history of hemorridectomy and 10% had a history of dilatation and curettage and cesarean section surgery. All patients had elevated E.S.R, Positive C-reactive protein and positive MRI finding. Conclusion, We must think of Pyogenic discitis in any patient with sever backache, fever, local tenderness, and high ESR